Hospitality sales and promotion : strategies for success - Taylor, Derek (Butterworth-Heinemann, 2015)
'Hospitality Sales and Promotion' is the essential guide for every manager in the hospitality industry wanting to achieve maximum profits from their sales promotions. Practical and down-to-earth, this guide discovers: * who is your customer? market segments and groups * how can you reach them effectively? the secrets of successful public relations * new and traditional technologies; from direct mail to using the Internet to maximum advantage. Derek Taylor has a wealth of experience in the hospitality industry and has worked with and advised numerous international corporate hospitality companies. Concrete and relevant case studies and examples from his experience are used to illustrate throughout the guide, from companies such as: Whitbread, Hilton International, Pizza Express and Stakis. An essential, practical and explanatory guide to sales promotion International case studies Well-known, experienced author.